Feldenkrais ‘Functional Integration’ Increases Body Contact Surface in the Supine Position: A Randomized-Controlled Experimental Study - Brummer, Matthias; Walach, Harald; Schmidt, Stefan (Frontiers in Psychology, 2018)
Feldenkrais ‘Functional Integration” (FI) is a widely used type of body work. We evaluated if a treatment with FI would induce changes in pressure and contact surface of the body on the mat. Thirty volunteers received an individual treatment with FI, in a randomised order on both sides of the body. Pressure and contact surface was documented with the Xsensor-Measurement-System. We found that pressure and contact surface significantly changed after the treatment (time p<0.0001; partial eta2=0.90). We also found that pressure and contact surface increased significantly on the left side for the group that started with the left side first (time x group p<0.016; partial eta2=0.62), and a tendency on the right side for the group that started with the right side first (time x group: p=0.056; partial eta2=0.54) Our results demonstrate that FI changes muscle tone affecting pressure and contact surface on the mat.